THE USE OF THE SPECIAL KNOWLEDGE IS DURING INVESTIGATION OF THE CRIMINAL OFFENCES RELATED TO THE STATE FINANCING OF INDUSTRY OF HEALTH PROTECTION IN THE CONDITIONS OF PANDEMIC - Харкевич, Ю.І. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2022)
The scientific article is devoted to the study of special knowledge, both its characteristics in general and the specifics of its use during the investigation of offenses related to public funding of the health care industry in the context of the Pandemic. Forms of the use of special knowledge, their classification at different times of the development of forensic science, in particular, the appointment of forensic examinations, are identified; reference and consulting activities; audits and other inspection reports; account verification; the involvement of a specialist in conducting procedural actions; interrogation of an expert; the presence of the investigator during the examination. Emphasis is placed on the importance of interdepartmental checks, interaction of law enforcement agencies with state financial control bodies. Based on the scientific points of view of scientists, an attempt was made to provide proposals for avoiding individual conflicts in the legislation regarding the assignment of audit and inventory to investigators. Attention is drawn to the use of monitoring, financial audit, procurement review and procurement monitoring. Also, certain aspects of the consultative form of using special knowledge and the participation of a specialist during some procedural actions under the specified category of criminal proceedings are disclosed. Forensic examinations are singled out, which are mainly appointed during the investigation of criminal offenses related to state funding of the health care industry in the context of a pandemic, including: economic, handwriting, technical examination of documents, computer and technical, telecommunications, commodity studies, video and sound recording, forensic, etc. All mentioned achievements are confirmed by statistical data and practical examples.

Використання спеціальних знань під час розслідування кримінальних правопорушень, пов’язаних із державним фінансуванням галузі охорони здоров’я в умовах Пандемії. Наукова стаття присвячена дослідженню спеціальних знань як їх характеристиці в цілому, так і специфіці використання під час розслідування правопорушень, пов’язаних із державним фінансуванням галузі охорони здоров’я в умовах Пандемії. Виствітлено форми використання спеціальних знань, їх класифікація в різні часи розвитку криміналістичної науки, зокрема, призначення судових експертиз; довідкова та консультаційна діяльність; ревізії та інші відомчі перевірки; перевірка за обліками; залучення спеціаліста при проведенні процесуальних дій; допит експерта; присутність слідчого при проведенні експертизи. Акцентовано на значенні міжвідомчих перевірок, взаємодії правоохоронних органів з органами державного фінансового контролю. На основі наукових точок зору науковців, зроблена спроба надати пропозиції щодо уникнення окремих колізій в законодавстві з приводу призначення ревізії та інвентарізації слідчим. Привернуто увагу до використання моніторінгу, фінансового аудиту, перевірки закупівель та моніторингу закупівлі. Також, розкрито окремі аспекти консультативної форми використання спеціальних знань та участі спеціаліста під час проведення деяких процесуальних дій за зазначеною категорією кримінальних проваджень. Виокремлено судові експертизи, які переважно призначаються при розслідуванні кримінальних правопорушень, пов’язаних із державним фінансуванням галузі охорони здоров’я в умовах пандемії, серед яких: економічна, почеркознавча, технічна експертиза документів, комп’ютерно-технічна, телекомунікаційна, товарознавча, відео та звукозапису, судово-медична тощо. Всі зазначені досягнення підтверджуються статистичними даними та практичними прикладами.
Використання спеціальних знань під час розслідування кримінальних правопорушень, пов’язаних із державним фінансуванням галузі охорони здоров’я у умовах пандемії
Keywords: the special knowledge; budgetary offences; health protection; pandemic; coronavirus; спеціальні знання; бюджетні правопорушення; охорона здоров’я; пандемія; коронавірус